Closing the Gap in Dysphagia Education: Rationale and Proposed Curriculum for an Undergraduate Course in Deglutition. - Evitts, Paul M. (Perspectives of the ASHA Special Interest Groups, 2026)
Swallowing disorders comprise a large percentage of the caseload for speech-language pathologists (SLPs), particularly in health care settings. However, this high percentage is incongruent with the amount of dysphagia coursework in most graduate curricula and the fact that dysphagia is a relatively recent addition to an SLP's scope of practice. The intent of this article is to provide information on the history and current state of dysphagia training, issues surrounding the current level of training, and, finally, a rationale and proposed curriculum for university programs to develop and implement an undergraduate course in deglutition.